Cathepsin G cleaves and activates IL-36γ and promotes the inflammation of psoriasis - Guo J; Tu J; Hu YY; Song GX; Yin ZQ (Dove Medical Press, 2019)
Jing Guo,1,* Jie Tu,1,* YingYing Hu,1,2,* GuoXin Song,3 ZhiQiang Yin1 1Department of Dermatology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, China; 2Department of Medical Cosmetology, Wuqing People’s Hospital, Wuqing, Tianjin, China; 3Department of Pathology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, China *These authors contributed equally to this work Background: IL-36γ is considered to be a valuable biomarker in psoriatic patients, which is expressed as an inactive precursor that needs to be proteolytically processed and activated, and neutrophil-derived proteases seemed to be potent activating enzymes of IL-36γ. Objectives: This study aims to investigate the activation of IL-36γ by cathepsin G (CG) and neutrophil elastase (NE). Materials and methods: We used inactive recombinant full-length (FL)-IL-36γ with different doses of NE or CG to stimulate HaCaT cells; neutrophil extracellular traps (NETs) were prepared to act on FL-IL-36γ and then stimulate HaCaT cells. Real-time quantitative PCR and ELISA were performed to detect CXCL-1 and CXCL-8 expression. We developed imiquimod-induced psoriasis-like mouse model to evaluate the effect of hypodermic injection of neutrophil-derived protease or its inhibitor. Histopathology and Western blotting were conducted for effect assessment. Results: Purified CG cleaved and activated recombinant human FL-IL-36γ to promote CXCL-1 and CXCL-8 expression by human keratinocytes, and NETs activated FL-IL-36γ and the activation was inhibited by serpin A3. CG induced expression of a more truncated IL-36γ in psoriasiform lesion of mice and aggravated the psoriasis-like lesion induced by imiquimod, whereas recombinant serpin A3 alleviated the severity of the psoriasis-like mouse mode. Conclusion: CG has the ability to cleave and activate IL-36γ and aggravate imiquimod-induced mouse psoriasiform lesion. Thus, CG-specific inhibitors might be promising therapeutic drugs for psoriasis. Keywords: psoriasis, IL-36, neutrophil, cathepsin, elastase